Cryopreservation Of Oncidium Golden Anniversary’s Protocorm-Like Bodies Using Encapsulation-Dehydration Method - Zakaria, Suhana (2019)
Oncidium Golden Anniversary is an orchid hybrid that has high economic value in flower market worldwide. However, this new orchid hybrid is difficult to maintain and cultivate conventionally thus increase the risk of permanent loss. Therefore, cryopreservation technique has been developed for long-term conservation of the orchids. This study was aimed to establish the proliferation of protocorm-like bodies (PLBs) and to develop encapsulation-dehydration method for cryopreservation of Oncidium Golden Anniversary hybrid orchid. The best media for rapid proliferation of PLBs was in half-strength semi-solid MS media supplemented with 20 g/L sucrose and 1 mg/L BAP using either whole PLBs, half-moon PLBs and transverse thin cell layer (tTCL) PLB as an explant. The PLBs produced were used as starting material in encapsulation-dehydration method and analysed by 2,3,5-triphenyltetrazolium chloride (TTC) spectrophotometry test and survivability percentage. Some important parameters have been assessed were PLB size, preculture condition, sodium alginate media, calcium chloride solution, dehydration duration, and the addition of antioxidants.